Translation as Multilingual Mediation in Local Islamic Higher Education: Evidence from Pre- and Post-Test Translation Tasks - Lilik Istiqomah (STKIP AGAMA HINDU SINGARAJA, 2026)
English Medium Instruction is widely associated with internationalization and wider access to academic knowledge, yet much less is understood about how students in local higher education contexts negotiate disciplinary meaning when academic content presented in English is mediated into Indonesian as the target language. This study explores that issue through translation practices in a local Islamic higher education setting. Drawing on pretest and posttest translation data, the analysis considers how students moved toward or away from meaning in terms of accuracy, acceptability, and comprehensibility. The findings suggest that improvement in translation quality varied across the data. In several cases, posttest versions conveyed academic ideas more clearly and rendered them in Indonesian in ways that were more natural and accessible. In other cases, however, revision did not substantially improve the translation, particularly when students were dealing with dense academic wording and complexity in phrases and clauses. These patterns suggest that the main challenge in this context is not simply vocabulary deficiency, but the mediation of disciplinary meaning across languages. Rather than viewing translation as evidence of weakness in English Medium Instruction, this study argues that it works as an intercultural bridge through which students connect English academic discourse with locally meaningful forms of understanding.